2021
DOI: 10.1186/s12916-021-02173-4
|View full text |Cite|
|
Sign up to set email alerts
|

P-gp expression inhibition mediates placental glucocorticoid barrier opening and fetal weight loss

Abstract: Background Prenatal adverse environments can cause fetal intrauterine growth retardation (IUGR) and higher susceptibility to multiple diseases after birth, related to multi-organ development programming changes mediated by intrauterine overexposure to maternal glucocorticoids. As a glucocorticoid barrier, P-glycoprotein (P-gp) is highly expressed in placental syncytiotrophoblasts; however, the effect of P-gp on the occurrence of IUGR remains unclear. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 77 publications
0
18
0
Order By: Relevance
“…32,33 Despite these beneficial effects, accumulating evidence showed that exposure of the fetus to active was related to adverse pregnancy outcomes, such as placental dysfunction, FGR, and reprogramming fetal organ development. 21,34,35 Taken together, we infer that excessive exposure to active GC may be one of the main causes of FGR induced by CA.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…32,33 Despite these beneficial effects, accumulating evidence showed that exposure of the fetus to active was related to adverse pregnancy outcomes, such as placental dysfunction, FGR, and reprogramming fetal organ development. 21,34,35 Taken together, we infer that excessive exposure to active GC may be one of the main causes of FGR induced by CA.…”
Section: Discussionmentioning
confidence: 75%
“…During pregnancy, appropriate exposure to GC not only is pivotal to enable the mother to meet the metabolic demands, 31 but also is crucial to accelerate the maturation of fetal lung for pregnant women with ongoing risk of premature delivery 32,33 . Despite these beneficial effects, accumulating evidence showed that excessive exposure of the fetus to active GC was related to adverse pregnancy outcomes, such as placental dysfunction, FGR, and reprogramming fetal organ development 21,34,35 . Taken together, we infer that excessive exposure to active GC may be one of the main causes of FGR induced by CA.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The involvement of P-gp in the brain has evolved to the point where it fights the entrance of neurotoxic medicines into the brain and hence maintains the penetration of central nervous system (CNS) agent delivery in the brain [54]. P-gp also protects the foetus against foreign bodies and hazardous chemicals entering the placenta [55].…”
Section: The Kinetics Of P-gpmentioning
confidence: 99%
“…The binding effect of modulators such as cyclosporine and verapamil are used in chemotherapy to modulate P-gp activity. The P-gp binding pockets' considerable flexibility and low specificity might be used to overcome MDR-related difficulties during chemotherapy [55]. P-gp inhibitors are classified primarily based on their specificity, affinity, and toxicity [64].…”
Section: Substrates Of P-gp and Its Drug Interactionmentioning
confidence: 99%